The impacts of workforce diversity on employee performance / Najwa Asilah Md Hamsani - Md Hamsani, Najwa Asilah (Faculty of Business and Management, 2014)
In today’s rapid changing business environment, countries like Malaysia have changed to accommodate the increasingly diverse work force. In general, the term “work force diversity” in the research can be defined as similarities and differences between employees in term of gender, age, ethnicity and education background. Therefore, this may influence employee’s work performance in an organization. Workplace diversity is a multi-faceted concept that will continue to evolve as more industries move toward a global marketplace which also led to a perception of being fundamental for employee performance. The purpose of this research is to investigate the impact of workforce diversity on employee performance in an organization which focus into manufacturing industry. The research focuses on workforce diversity which includes the gender, age, ethnic and education background of the employees. The investigation was done by distributing 86 questionnaires to the employee of GG Circuits Industries Sdn. Bhd.